The Predictive Value of Peripheral Immune Cell Counts for the Presence of Brain Metastases in Stage IV Non-Small-Cell Lung Cancer (NSCLC) - Abuelbeh, I; Abu-Shawer, O; Abu-Shawer, M; Alkderat, M; Safi, M; Alwazani, A; Alkhatib, A; Abu-Hussain, B; Aladawi, M; Ismail, S; Altamimi, T; Abu Hejleh, Taher (Avicenna Journal of Medicine, 2022)
Background High neutrophil–lymphocyte ratio (NLR) is associated with poor survival in lung cancer. This study evaluates whether NLR is associated with baseline brain metastasis in stage IV non-small cell lung cancer (NSCLC).Methods Medical records of stage IV NSCLC patients treated at King Hussein Cancer Center (Amman-Jordan) between 2006 and 2016 were reviewed. Patients with baseline brain imaging and complete blood count (CBC) were included. Receiver operating characteristic (ROC) curve was used to identify the optimal cutoff value for the association between NLR and baseline brain metastasis. Association between age, gender, location of the primary tumor, histology, and NLR was assessed using univariate and multivariate logistic regression analyses.Results A total of 722 stage IV NSCLC patients who had baseline brain imaging were included. Median age was 59 years. Baseline brain metastasis was present in 280 patients (39.3%). Nine patients had inconclusive findings about brain metastasis. The ROC curve value of 4.3 was the best fitting cutoff value for NLR association with baseline brain metastasis. NLR ≥ 4.3 was present in 340 patients (48%). The multivariate analyses showed that high baseline NLR (≥ 4.3) was significantly associated with higher odds of baseline brain metastasis (odds ratio [OR]: 1.6, 95% confidence interval [CI]: 1.2–2.2; p = 0.0042). Adenocarcinoma histology was also associated with baseline brain metastasis (OR: 0.4, 95% CI: 0.25–0.6; p = 0.001).Conclusion High NLR is associated with baseline brain metastasis in advanced-stage NSCLC. In the era of immunotherapy and targeted therapies, whether high NLR predicts response of brain metastasis to treatment is unknown.
Keywords: NSCLC; neutrophil–lymphocyte ratio; brain metastasis; stage IV